2017
DOI: 10.1038/s41598-017-01599-2
|View full text |Cite
|
Sign up to set email alerts
|

Crop yield response to climate change varies with crop spatial distribution pattern

Abstract: The linkage between crop yield and climate variability has been confirmed in numerous studies using statistical approaches. A crucial assumption in these studies is that crop spatial distribution pattern is constant over time. Here, we explore how changes in county-level corn spatial distribution pattern modulate the response of its yields to climate change at the state level over the Contiguous United States. Our results show that corn yield response to climate change varies with crop spatial distribution pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
71
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 133 publications
(75 citation statements)
references
References 57 publications
2
71
0
2
Order By: Relevance
“…At the national level, we found no clear effect of high temperature on yield. More importantly, national level effects can be misleading if the underlying geographic distribution of the crop changes (Leng and Huang 2017). In China, the effect of high temperature was negative in the south and positive in the north.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the national level, we found no clear effect of high temperature on yield. More importantly, national level effects can be misleading if the underlying geographic distribution of the crop changes (Leng and Huang 2017). In China, the effect of high temperature was negative in the south and positive in the north.…”
Section: Discussionmentioning
confidence: 99%
“…Possible future climate change driven changes in the spatial distribution of crops have been modeled (Leemans and Solomon 1993, Hannah et al 2013, Shabani and Kotey 2016, but there has been little research on historical changes in crop distribution and climate and how these interact to affect crop yield (e.g. Leng andHuang 2017, Qiao et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in the northeast region of China, global warming modeling forecasted that the extreme temperature increase (where temperature increases by 1.32 • C) would lead to a decrease in maize production by~35% in 2030 as compared to productivity in 2008 [72]. In the United States, global warming has resulted in an average 2.5% decrease in maize yield in the period from 1970 to 1999, and precipitation modeling reported that by the 2050s, corn yields are projected to decrease further by 20 to 50% depending on the current emission scenarios [73]. Water supply is also a vital factor for maize production.…”
Section: Maizementioning
confidence: 99%
“…Empirical models (both process-based simulation models and statistical models) have been used to assess the potential impacts of weather on crop yields [19]. For example, a comprehensive data-driven analysis is developed to investigate crop pattern between counties in regulating corn yield response to weather change at the state level of U.S [20]. The issue of land use change and agricultural crop acreage response due to economic and biophysical factors is well documented focusing on Northern Great Plains agriculture [21,22].…”
Section: Introductionmentioning
confidence: 99%